(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Objective: Premature uterine contraction caused by spontaneous rupture of subserous uterine vein resulting intrauterine asphyxia. Method & Results: A primigravida with uneventful pregnancy having regular antenatal care attended a private clinic at her 38 week of pregnancy with slight pain in whole abdomen and hardening of uterus. After giving rest in left lateral position & oxygen inhalation, hardening of uterus persisted. By that time she developed fetal tachycardia and had to undergo caesarean section, there was hemoperitonum and an asphyxiated male baby was delivered. On exploration a subserous uterine vein was detected on the posterior wall of the uterus. Complete hemostasis was achieved with interrupted sutures and electrocauterization of the bleeding points. Post-operative period was uneventful for the mother but the baby was managed in neonatal care unit. Both of them were well during discharge. Conclusion: Monitoring of pregnant women at last trimester is very important. Any deviation from normal like hardening of uterus should be carefully taken care of for good maternal and fetal outcome. Bangladesh J Obstet Gynaecol, 2012; Vol. 27(2) : 87-89